Meaning and Follow Up of Positive Fictional Decisions According to the Government Administration Law - Syamsir Syamsu; Muhammad Alifian Geraldi Fauzi (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
After enacting the Government Administration Law, there have been positive fictitious decisions, which are contrary to the negative fictitious decisions stipulated in the Administrative Court Law. It has led to an inaccurate understanding in some of the general public that a positive decision is the final form of a request from the public to a government agency or official being granted a decision and/or implementation of government action. This research uses normative legal research methods using a statutory approach and literature study. This study explains that the existence of positive fictional decisions does not necessarily eliminate the existence of negative fictional decisions.